2011
DOI: 10.1039/c1pp05100h
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide-modified liposomes for bacteria targeted delivery of temoporfin in photodynamic antimicrobial chemotherapy

Abstract: Photodynamic antimicrobial chemotherapy (PACT) and antimicrobial peptides (AMPs) are two promising strategies to combat the increasing prevalence of antibiotic-resistant bacteria. To take advantage of these two strategies, we integrated a novel antimicrobial peptide (WLBU2) and a potent generation II photosensitizer (temoporfin) into liposomes by preparing WLBU2-modified liposomes, aiming at bacteria targeted delivery of temoporfin for PACT. WLBU2 was successfully coupled to temoporfin-loaded liposomes using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 50 publications
(40 reference statements)
1
53
0
Order By: Relevance
“…Alternatively Zn 2 BDPA coated liposomes may have potential as antibiotic delivery vehicles. 50,51 The selectivity for anionic cell surfaces was further demonstrated by selective staining of dead or dying mammalian cells in the presence of healthy cells, an experimental outcome that is consistent with the targeted liposome results of others. 5254 While Zn 2 BDPA coated liposomes could simply be employed as dead cell stains for in vitro assays, we envision a more ambitious in vivo application as a cell death “theranostic” platform that combines therapeutic and diagnostic capabilities within a single nanoparticle.…”
Section: Resultssupporting
confidence: 80%
“…Alternatively Zn 2 BDPA coated liposomes may have potential as antibiotic delivery vehicles. 50,51 The selectivity for anionic cell surfaces was further demonstrated by selective staining of dead or dying mammalian cells in the presence of healthy cells, an experimental outcome that is consistent with the targeted liposome results of others. 5254 While Zn 2 BDPA coated liposomes could simply be employed as dead cell stains for in vitro assays, we envision a more ambitious in vivo application as a cell death “theranostic” platform that combines therapeutic and diagnostic capabilities within a single nanoparticle.…”
Section: Resultssupporting
confidence: 80%
“…Temoporfin liposomes conjugated with a specific lectin (wheat germ agglutinin, WGA) on the liposomal surface eradicated all MRSA by PDT compared with non-modified liposomes [57]. A new PS integrated a potent second generation photosensitizer (temoporfin) and a novel antimicrobial peptide (WLBU2) into liposomes that killed all MRSA upon illumination with 652 nm laser (1 W/cm 2 , 100 s, 100 J/cm 2 ) [58]. Tsai et al showed that 0.25 μM micellar hematoporphyrin (Hp) completely eradicated S. aureus under a light fluence of 50 J/cm 2 [59].…”
Section: Photodynamic Therapy As An Anti-infectivementioning
confidence: 99%
“…Moreover, a targeting of various antimicrobial agents by means of liposomes is in the forefront of the research of the treatment of infections that prove refractory to conventional forms of antimicrobial agents, such as amphotericin B, nystatin, or macrolide [15,16]. Liposomal encapsulation also offers an efficient way of delivery of antimicrobial peptides, as has been shown by Yang et al on a methicillin-resistant Staphylococcus aureus (MRSA) [17]. Thus, we hypothesized that the cationic nature of the complexes formed by PMPs and cationic liposomes may improve the interactions with the bacterial membranes, and, hence, it may be useful in bacterial infection treatment [18].…”
Section: Introductionmentioning
confidence: 99%